2012
DOI: 10.1128/jvi.01963-12
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Allele-Specific PCR Reveals Rare Preexisting Drug-Resistant Variants and a Large Replicating Virus Population in Macaques Infected with a Simian Immunodeficiency Virus Containing Human Immunodeficiency Virus Reverse Transcriptase

Abstract: It has been proposed that most drug-resistant mutants, resulting from a single-nucleotide change, exist at low frequency in human immunodeficiency virus type 1 (HIV-1) and simian immunodeficiency virus (SIV) populations in vivo prior to the initiation of antiretroviral therapy (ART). To test this hypothesis and to investigate the emergence of resistant mutants with drug selection, we developed a new ultrasensitive allele-specific PCR (UsASP) assay, which can detect drug resistance mutations at a frequency of >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Despite waning RPV plasma concentrations and lack of complete virus suppression, which may be seen in noncompliant individuals and suggesting suboptimal in vivo drug inhibition, persistent DRMs were not selected in the plasma or tissues of either animal after RPV LA administration. This is in contrast to our previous studies, in which EFV monotherapy was administered over 4 days in RT-SHIV-infected macaques and rapidly selected the NNRTI resistance mutation K103N in the plasma virus that affected the efficacy of subsequent combination therapy containing EFV, particularly in two animals with high plasma viremia levels similar to the animals in this study (30,40,62). Another study using a different strain of RT-SHIV in rhesus macaques also showed that K103N and other DRMs arise during EFV monotherapy (34).…”
Section: Discussioncontrasting
confidence: 95%
“…Despite waning RPV plasma concentrations and lack of complete virus suppression, which may be seen in noncompliant individuals and suggesting suboptimal in vivo drug inhibition, persistent DRMs were not selected in the plasma or tissues of either animal after RPV LA administration. This is in contrast to our previous studies, in which EFV monotherapy was administered over 4 days in RT-SHIV-infected macaques and rapidly selected the NNRTI resistance mutation K103N in the plasma virus that affected the efficacy of subsequent combination therapy containing EFV, particularly in two animals with high plasma viremia levels similar to the animals in this study (30,40,62). Another study using a different strain of RT-SHIV in rhesus macaques also showed that K103N and other DRMs arise during EFV monotherapy (34).…”
Section: Discussioncontrasting
confidence: 95%
“…This time point was chosen to allow seeding of the residual viral reservoir while limiting the opportunity of the virus to develop and archive drug resistance variants, as has been shown for SHIVmne-infected animals prior to the initiation of ART (77) and may be more likely in the setting of the very high replication rates of SIVmac239. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells infected by HIV-1 per day is on the order of 10 7 (23), but the number of viruses contributing to the next generation might be considerably smaller due to the burstiness of replication. Recent evidence points to a relevant population size in excess of the inverse mutation rate (27). In fact, the evolutionary dynamics depends only weakly on the actual value of the population size N once the product N is of order one or larger (28).…”
Section: Sequence Data Collectionmentioning
confidence: 99%